The oidores of the Royal Audience of Lima in the second half of the 16th century - Angeli, Sergio (2008)
The American Courts played a fundamental role in the social and political life of the Castilian colonies. As the highest court in civil and criminal matters, the Audiencias had an enormous gravitation in colonial society. Its magistrates were a fundamental part of the life of the Viceroyalties, adding prestige and intellectual luster to the local elites. A wide range of prohibitions hung over the oidores, in order to avoid contact with the surrounding society. Despite them, the colonial judges actively participated in business, were compadres, godparents and benefactors of a wide range of Spaniards settled in Lima. No business escaped, apparently, from its gravitation and influence. This is how they managed to become the cream of the crop of the American Viceroyalties. Between 1549 and 1564 the Lima hearers took charge of the colonial government on three occasions. During that period the magistrates managed to increase their power and social influence. This work will attempt to analyze the formation of the Audiencia de Lima, the ways in which justice was issued and the relationships that were maintained with the Peruvian colonial society. The superimposition of functions that the high Indian judiciary had exemplifies the stagnant practices of favors and corruption that were formed around legal practice. In this sense, it will try to reveal the actions of the lawyers inserted in a network of relationships that affected the entire social environment and that lasted in subsequent centuries.